2011
DOI: 10.1038/gt.2011.165
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-targeted microbubble destruction enhances naked plasmid DNA transfection in rabbit Achilles tendons in vivo

Abstract: The study was to investigate the probability of increasing the transfection of the gene in tendons by ultrasound-targeted microbubble destruction (UTMD), and to search for the most suitable transfection conditions. A mixture of microbubbles and enhanced green fluorescent protein (EGFP) plasmids was injected into rabbit Achilles tendons by different administration routes and the tendons were ultrasound pulse by different ultrasonic conditions in order to determine the most appropriate conditions. Then, the rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The mechanical effect of ultrasound allows increases in biomembrane permeability and changes in membrane potential (Junqueira et al, 1979;Beeri et al, 2002;Li et al, 2003;Chappell et al, 2008;Yuan et al, 2011;Qiu et al, 2012). The non-thermal effect is related to cavitation, and such cavitation may lead to strong viscous stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical effect of ultrasound allows increases in biomembrane permeability and changes in membrane potential (Junqueira et al, 1979;Beeri et al, 2002;Li et al, 2003;Chappell et al, 2008;Yuan et al, 2011;Qiu et al, 2012). The non-thermal effect is related to cavitation, and such cavitation may lead to strong viscous stress.…”
Section: Discussionmentioning
confidence: 99%
“…(4) A total of 500 mg of plasmid DNA in 0.5 mL solution was injected to the five sites (each site received 100 mg of plasmid DNA) along the LV free wall, including four sites at the middle to lower part of the free left ventricular wall and one site at the tip of the heart. A US catheter was used to insonate each site in the EGFP-US group; insonation was conducted for 30 s, with a 10 s pause, at 4.3 MHz and 1 W/cm 2 , and the total insonation time was 60 s (Qiu et al, 2012). In the EGFP alone group, the gene was injected into the myocardium without insonation.…”
Section: Transendocardial Plasmid Pegfp Transfermentioning
confidence: 99%
“…A number of nonsurgical treatments have been explored, including medication, physiotherapy and steroid hormone injection, to promote tendon healing, but none of these methods is really effective or has been widely applied clinically. 3 Tissue growth factors can regulate cell proliferation, migration of fibroblasts, differentiation and matrix synthesis and have the potential to directly influence cellular mitogenesis, thus having an important role in tendon repair. [3][4] Insulin-like growth factor-1 (IGF-1) induces tenocyte migration and division, matrix expression and collagen synthesis, thus having the potential to enhance wounded tendon regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…3 Tissue growth factors can regulate cell proliferation, migration of fibroblasts, differentiation and matrix synthesis and have the potential to directly influence cellular mitogenesis, thus having an important role in tendon repair. [3][4] Insulin-like growth factor-1 (IGF-1) induces tenocyte migration and division, matrix expression and collagen synthesis, thus having the potential to enhance wounded tendon regeneration. 4 Many studies 5 have demonstrated that IGF-1 can promote tendon repair and enhance wounded tendon regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation